Penerapan Teknik Relaksasi Nafas Dalam Terhadap Tingkat Skala Dismenorea Pada Remaja Di SMAN 2 Karanganyar - Rimma Wahyuni Khumayroh; Erika Dewi Noorratri (Pusat Riset dan Inovasi Nasional, 2023)
Background: Dysmenorrhea is a feeling of discomfort in the lower abdomen spreading to the waist that is often experienced by young women that occurs before and during menstruation, usually accompanied by nausea. The deep breathing relaxation technique is a complementary therapy that teaches how to take deep breaths, maximally hold inspiration and how to exhale slowly. Purpose: Knowing the changes in the level of the dysmenorrhea scale in adolescents before and after doing deep breathing relaxation techniques. Method: This application uses a descriptive research method and observes events or events that have occurred. Descriptive research is research conducted to describe or describe an event that occurs in society. Results: Treatment of dysmenorrhea with deep breathing relaxation techniques given 5 times for 15 minutes can affect the level of dysmenorrhea so that there is a change in the level of the pain scale in adolescents. Conclusion: Deep breathing relaxation techniques can reduce the level of dysmenorrhea in adolescents who are experiencing menstrual pain.